Spiritual care at the crossroads: an ecumenical white paper on the future of Christian healthcare chaplaincy - Peng-Keller, Simon; Balboni, Michael J.; Balboni, Tracy A.; Haußmann, Annette; Haythorn, Trace; Mösli, Pascal; Neuhold, David; Nuzum, Daniel R.; Smeets, Wim; Swift, Christopher; Swinton, John; Roser, Traugott; et al. (Journal of religion and health, 2025)
This ecumenical White Paper aims to clarify the profile of Christian healthcare chaplaincy in a context of rapidly changing healthcare systems. The increasing complexity and specialization of healthcare, the shift towards outpatient care, mounting economic pressures, the demographic and epidemiological transitions towards chronic and elderly care, and global health crises are profoundly transforming and challenging Christian healthcare chaplaincy. At the same time, the societal context of healthcare chaplaincy is also changing rapidly. While church resources and influence are declining, spiritual and religious diversification is on the rise. This paper engages with this rapid change as a moment of opportunity. It addresses the role of Christian healthcare chaplains in a time of change and clarifies their theological basis, their professional competencies, and the future of their education and training.